PENGEMBANGAN PAKET ALAT PERAGA TERPADU MELALUI LIFESKILL PROJECT UNTUK MENINGKATKAN KETERAMPILAN CALON GURU FISIKA DALAM MEMFASILITASI PENDEKATAN SAINTIFIK - Nur Khoiri; Susilawati . (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2014)
Activity observed and tried in the stage scientific approach requires the availability of props to demonstrate concepts and try the content to be learned. The problem by prospective physics teachers is the difficulty in making simple physics props needed at this stage and try to observe the implementation of the scientific approach. The objectives of this research is that the physics teacher candidates have the skills to design a simple physics props relevant to 21st century skills. This study is a Research and Development (R&D). The result product is a package props to static and dynamic fluid. This study was conducted based on the analysis of the needs prospective physics teachers to have certain skills (soft skills) and the ability to facilitate learners to explore. This study resulted in an integrated props for the concept of fluid through projects such as Torricelli hydrostatic pressure, venturi pipe, hydraulic bridge, liquid viscosity, and hydraulic pipes. The results of the expert validation revealed that this integrated props recommended for use as props and lab equipmentin fluid concept. Validation of experts found that the relevance of the material props, the practically of the use of props, language and time including both categories. The results of limited test package props fluid shows that there is an increase in the study of students after using the fluid package props. Key words: props, lifeskill project, skills, scientific approach